EXPRESS: Decoding Interdependent DApp Adoption Decisions: The Moderating Role of Governance Mechanisms on Blockchain Platforms - Cai, Xudong; Zhang, Bin; Zhao, Xi; Feng, Gengzhong (Production and Operations Management, 2026)
Decentralized applications (DApps)—digital applications operating on blockchain platforms—are transforming diverse industrial sectors. As blockchain platforms feature protocol-based governance, the mechanisms driving DApp adoption differ fundamentally from those in traditional digital environments. Drawing on observational learning theory, we conceptualize individual DApp adoption as decision interdependence driven by the visible actions of others. Building on platform governance theory, we identify three core governance-driven characteristics—decentralization, trustlessness, and token incentives—as key contextual moderators of this interdependence. We empirically investigate these dynamics on Ethereum, the world’s largest DApp platform, leveraging an unprecedented dataset covering its entire history through July 2025. Our findings confirm that decision interdependence is a significant driver of individual DApp adoption decisions, and that this effect is further amplified by blockchain’s unique governance characteristics: the effect of decision interdependence strengthens with higher decentralization and higher trustlessness, and is more pronounced for DApps offering token incentives. Extensive robustness checks, including DID and DDD analyses, alternative measures of blockchain characteristics, and accounting for copycat competition, reinforce these findings. By uncovering how blockchain’s distinctive governance mechanisms reshape decision interdependence, this study advances technology adoption theory beyond socially embedded settings and highlights how platform design fundamentally conditions user decision-making. Platform designers and DApp developers can leverage these insights to strategically calibrate blockchain governance features to amplify peer-driven adoption, advancing the operations management literature on blockchain-enabled digital platforms.